Association of CFH and SERPING1 polymorphisms with anterior uveitis. Issue 11 (21st August 2013) - Yang, Ming-ming; Lai, Timothy Y Y; Tam, Pancy O S; Chiang, Sylvia W Y; Ng, Tsz Kin; Rong, Shi Song; Pang, Chi Pui
Abstract : Aims: To investigate the association of the complement factor H ( CFH ) and complement component 1 inhibitor ( SERPING1 ) genes with anterior uveitis (AU). Methods: A total of 406 subjects (98 patients with AU and 308 controls) were recruited for this study. Two CFH polymorphisms (rs3753394 and rs1065489) and two SERPING1 polymorphisms (rs1005511 and rs3824988) were genotyped using TaqMan genotyping assays. Analyses were stratified for gender and human leukocyte antigen (HLA)-B27 status. Correlations of the genotypes with multiple clinical features were also evaluated. Results: No significant association was found between any of the four polymorphisms and AU after multiple testing corrections. However, stratified analyses showed that there were significant increases in the frequencies of T allele and TT homozygosity for CFH -rs1065489 in female patients compared with that of controls (pcorr =0.004 and pcorr =0.012 respectively). In addition, CFH -rs1065489 was also associated with AU in patients who were HLA-B27 positive. No significant association with AU was found for the other three single nucleotide polymorphisms (SNPs), even stratified by gender or HLA-B27 status. Genotype–phenotype analyses found that CFH -rs1065489 TT genotype was associated with higher uveitis recurrence frequency. No correlation was found between CFH -rs1065489 and other clinical features. Conclusions: This study revealed an association of CFH -rs1065489 with AU as well as uveitis recurrence frequency. The influence on AU could be gender specific and dependent on HLA-B27 status. Our results also suggested that SERPING1 does not play a significant role in the development of AU.